The Organization of Islamic Cooperation and human rights - Petersen, Marie Juul; Kayaoglu, Turan (Pennsylvania studies in human rights, 2019)
Founded in 1969, the Organization of Islamic Cooperation (OIC) is an intergovernmental organization whose purpose is the strengthening of solidarity among Muslims. With expectations as to the OIC's role in global human rights that are, to date, unfulfilled, this volume demonstrates the potential, obstacles, and shortcomings of the OIC